Optimization of Wet Noodle Formulation Fortified with Spirulina platensis L. Powder Using D-Optimal Mixture Design: Optimasi Formula Produk Mi Basah Terfortifikasi Bubuk Spirulina platensis L. Menggunakan D-Optimal Mixture Design - Setyawan, Hendrix Yulis; Eka Wahyu Belianna; Afifal, Lana Izzatul; Damayanti, Devi Dwi; Shafira, Dhea Aura Bening; Wijayanti, Karlina (Jurnal Pangan dan Agroindustri, 2025)
Abstract The productive life of Indonesian people encourages the consumption of cheap and practical instant noodles, with 3.8% consuming them more than once a day. However, the low protein content of instant noodles requires fortification, one of which is with Spirulina platensis powder which contains high protein up to 71.90%. This study aims to determine the optimum proximate conditions of wet noodles fortified with spirulina powder using Design Expert 13 software with the D-optimal mixture design method. The variables tested were spirulina powder with an upper limit of 3.75 grams and a lower limit of 0 grams, and tapioca flour with an upper limit of 7.5 grams and a lower limit of 3.75 grams. The results of statistical tests showed that spirulina powder was significant on protein and carbohydrate levels (F<0.05), but not significant on water, ash, and fat levels (F>0.05). The best formulation was obtained at 3.75 grams of tapioca and 3.75 grams of spirulina with a water content of 32.06%, ash 2.49%, protein 18.96%, fat 1.78%, carbohydrate 44.71% which met the wet noodle standards in SNI 01-2987-2015.   Abstrak Kehidupan produktif masyarakat Indonesia mendorong konsumsi mi instan yang murah dan praktis, dengan 3,8% mengonsumsinya lebih dari sekali per hari. Namun, kandungan protein mi instan yang rendah memerlukan fortifikasi, salah satunya dengan bubuk Spirulina platensis yang mengandung protein tinggi hingga 71,90%. Penelitian ini bertujuan untuk menentukan kondisi optimum proksimat mi basah terfortifikasi bubuk spirulina menggunakan software Design Expert 13 dengan metode D-optimal mixture design.  Variabel yang diuji adalah bubuk spirulina dengan batas atas 3,75 gram dan batas bawah 0 gram, serta tepung tapioka dengan batas atas 7,5 gram dan batas bawah 3,75 gram. Hasil uji statistik menunjukkan bubuk spirulina signifikan terhadap kadar protein dan karbohidrat (F<0,05), tetapi tidak signifikan terhadap kadar air, abu, dan lemak (F>0,05). Formulasi terbaik diperoleh pada 3,75 gram tapioka dan 3,75 gram spirulina dengan kadar air 32,06%, abu 2,49%, protein 18,96%, lemak 1,78%, dan karbohidrat 44,71% yang telah sesuai standar mi basah pada SNI 01-2987-2015.